2007
DOI: 10.1021/jm070836d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Structural and Conformation Modifications, Including Backbone Cyclization, of Hydrophilic Hexapeptides on Their Intestinal Permeability and Enzymatic Stability

Abstract: A library of 18 hexapeptide analogs was synthesized, including sub-libraries of N- or C-methylation of the parent hexapeptide Phe-Gly-Gly-Gly-Gly-Phe, as well as backbone cyclized analogs of each linear analog with various ring sizes. N- or C-methylation as well as cyclization (but not backbone cyclization) have been suggested to improve intestinal permeability and metabolic stability of peptides in general. Here we aimed to assess their applicability to hydrophilic peptides. The intestinal permeability (Papp)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 52 publications
0
83
0
8
Order By: Relevance
“…125129 To understand specific effects of conformation on peptide uptake in gut epithelium, explicit comparisons were made among sets of cyclic peptides, turn peptides, and N-methylated peptides using Caco-2 cells. 126,127,130 These studies showed that conformation can powerfully alter permeability in ways that cannot be fully attributed to physicochemical factors. Later development of artificial membranes, including the parallel artificial membrane permeability assay (PAMPA), 131 has helped to further deconvolute transcellular, paracellular, and active transport mechanisms and better explain peptide uptake.…”
Section: Shape Sorters: Systematic Studies Using Model Systemsmentioning
confidence: 99%
“…125129 To understand specific effects of conformation on peptide uptake in gut epithelium, explicit comparisons were made among sets of cyclic peptides, turn peptides, and N-methylated peptides using Caco-2 cells. 126,127,130 These studies showed that conformation can powerfully alter permeability in ways that cannot be fully attributed to physicochemical factors. Later development of artificial membranes, including the parallel artificial membrane permeability assay (PAMPA), 131 has helped to further deconvolute transcellular, paracellular, and active transport mechanisms and better explain peptide uptake.…”
Section: Shape Sorters: Systematic Studies Using Model Systemsmentioning
confidence: 99%
“…Through backbone cyclization, a range of cyclic derivatives of a given peptide sequence can be designed and studied, by changing the size and position, as well as the chemical nature of the connecting bridge. Gradual variations in the ring size can be achieved by the introduction of preformed building blocks, such as N-or C-alkylated amino acids of different lengths and residues bearing a w-functional alkylene moiety on a backbone nitrogen (FiguRe 11) [90]. An additional variable can be introduced in the nature of the bridge; most commonly lactam, disulfide or thioether bridges.…”
Section: Backbone Cyclization and Cycloscanmentioning
confidence: 99%
“…This selection method is known as cycloscan. Backbone cyclization has been shown to enhance the metabolic stability of several natural peptides, including substance P [90], somatostatin [91], pheromone biosynthesis-activating neuropeptide [92,93] and Tat [89]. Recently, it was shown that backbone cyclization results in an enhancement of paracellular intestinal permeability and stability toward enzymatic degradation, compared with linear analogs [90].…”
Section: Backbone Cyclization and Cycloscanmentioning
confidence: 99%
“…In addition, it enhances intestinal permeability by the paracellular mechanism [82]. Beyond that, backbone cyclic analogs of aMSH were found to be receptor-selective, metabolically stable and orally available [10].…”
Section: Backbone Cyclic Analogsmentioning
confidence: 99%